FORMULASI GRANUL ANTIDIARE DARI EKSTRAK ETANOL DAUN KRATOM ( Mitragyna spesioca Korth) - dian kartikasari; suhaimi suhaimi (Jurnal Insan Farmasi Indonesia, 2019)
Indonesian medicinal plants have been used both as traditional Indonesian medicine (herbal medicine), standardized herbal medicines or phytopharmaca. ethanol extract of kratom leaf (Mitragyna speciosa Korth) has been able to inhibit the growth of Escherichia coli bacteria and therefore researchers have developed a formula that is used as antidiarrheal, namely kratom leaf extract granule. The purpose of the concentration is avicel pH 101 that affects the physical properties of kratom leaf extract granules and on what formula meets the physical properties requirements of kratom leaf extract granules. The method used is the wet granulation method. With the ingredients used 5% kratom extract, evicel pH 101 and aerocil. By looking for the best aerosil pH 101 results and the best extract of kratom leaves, then the moisture content, flow time, angle of rest, and pH of the granule solution were evaluated. As for the results it can be concluded that the test carried out with 15% avicel concentration has a good effect on the physical granule Obtained the best formula is formula IV, it can be seen based on the test results fulfilling the granule requirements.